2005
DOI: 10.1097/01.mib.0000160810.76729.9c
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Performance in Patients With Crohnʼs Disease in Clinical Remission

Abstract: CD patients in clinical remission have decreased muscle function that may affect their quality of life. This pattern is reflected by reduced strength and endurance indexes, particularly for lower limbs. The reasons for these changes need further study. Strength training should be assessed in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(117 citation statements)
references
References 38 publications
5
110
0
2
Order By: Relevance
“…In this issue, Salacinski et al [5] have objectively demonstrated reduced lower limb muscle strength in subjects with Crohn's disease (CD) compared to healthy controls, confirming the work of previous studies [6,7]. However, the study was unable to show that this reduced strength was directly attributable to lower vitamin D (25-(OH) or vitamin D3) levels in CD subjects as originally hypothesized.…”
Section: Introductionsupporting
confidence: 56%
“…In this issue, Salacinski et al [5] have objectively demonstrated reduced lower limb muscle strength in subjects with Crohn's disease (CD) compared to healthy controls, confirming the work of previous studies [6,7]. However, the study was unable to show that this reduced strength was directly attributable to lower vitamin D (25-(OH) or vitamin D3) levels in CD subjects as originally hypothesized.…”
Section: Introductionsupporting
confidence: 56%
“…Compared with healthy controls in Crohn's disease skeletal muscle mass and strength are reduced (87)(88)(89) and muscle fatigue is increased (90) . Fatigue is a major concern in Crohn's disease (91)(92)(93)(94) with two of five patients reporting that it negatively impacts their QoL, even in remission (95) .…”
Section: Clinical Studies; Association Between 25-hyroxyvitamin D Levmentioning
confidence: 95%
“…We also identified several pathways related with cellular catabolic process and muscle development. Abnormal cellular metabolic process could cause increased energy expenditure, which are typically shown in patients with CD and could further alter muscle mass and function with persist nutritional deficiencies [40]. However, given the fact that there still lacks a complete understanding of the etiology of CD, it is difficult to provide a conclusive evaluation, which will be studied in our future research.…”
Section: Resultsmentioning
confidence: 99%